The Effects of Selective Harvest on Exploited Population and Economic Benefits - Sun, Peng; Yu, Jie; Sun, Runlong; Liu, Guankui; Xi, Xiaoyu; Tian, Yongjun (Frontiers in Marine Science, 2022)
The composition of catch is affected by exploited fishing gear and its selectivity, and long-term selective harvest induces the change of biological characters and economic value of exploited population. Stow net is the main fishing gear to capture commercially important fish species small yellow croaker (Larimichthys polyactis) in Haizhou Bay, China. Long-term stow net selective harvest affects both the biological characters and economic benefits of small yellow croaker. Therefore, an appropriate harvest scenario that can achieve the high economic benefits and the sustainable use needs to be explored. In this study, we develop a bio-economic model for small yellow croaker and focus on different harvest scenarios for obtaining maximum economic benefit and sustainable utilization of resource. Our results indicate that the increase of mesh size has positive effects on the protection of small yellow croaker population, and optimal harvest scenario achieves the short- or long-term economic benefits to different stakeholders. Fishing with small mesh size gets high economic value in short-term, while fishing with large mesh size achieves better economic value and effectively protect small yellow croaker resource under long-term fishing pressure. This study provides evidence to balance the long-term economic benefits and sustainable utilization of fishery resource, and it also offers a basis for the scientific formulation of fishery policy.